Treatment of depression during pregnancy: a protocol for systematic review and meta-analysis - Junkes, Larissa; Gherman, Bruno Rabinovici; Appolinario, Jose Carlos; Nardi, Antonio Egidio (Frontiers in Psychiatry, 2024)
Introduction: Major Depressive Disorder (MDD) is a chronic, recurrent, and highly prevalent disease that is associated with significant functional disability. During pregnancy, the prevalence of the disease is approximately 20%, with 12% of these, requiring treatment to avoid important negative consequences for the mother-baby binomial. Risk-benefit assessment of the use of antidepressants during pregnancy is mandatory, in addition to knowledge of the long-term effects of prenatal exposure to these drugs in the offspring. In this study, we will perform an updated systematic review and meta-analysis to explore the treatment of depression during pregnancy, along with its effectiveness, safety, and possible harm to women and children.We will search for publications in the following databases: Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, Web of Science, Scopus, Lilacs, and PsycINFO. The reference lists of the included studies will be manually reviewed to identify potentially relevant studies. There will be no restrictions on language or date of publication. Quality assessment of the included studies will be performed independently according to the Cochrane Risk of Bias (RoB2) instrument. To assess the certainty of the findings' body of evidence, we will use the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. This study aimed to ascertain the efficacy and safety of antidepressants in pregnant women and children.Ethics and dissemination: Ethical approval was not required as individual patient data were not collected. Dissemination: Plan to publish a systematic review in an open-access medical journal at the end of the process.